Answer:
2 x^2 - 3 x + 6
Step-by-step explanation:
Simplify the following:
-(3 x^2 + 4 x - 17) + 5 x^2 + x - 11
-(3 x^2 + 4 x - 17) = -3 x^2 - 4 x + 17:
-3 x^2 - 4 x + 17 + 5 x^2 + x - 11
Grouping like terms, 5 x^2 - 3 x^2 + x - 4 x - 11 + 17 = (5 x^2 - 3 x^2) + (x - 4 x) + (-11 + 17):
(5 x^2 - 3 x^2) + (x - 4 x) + (-11 + 17)
5 x^2 - 3 x^2 = 2 x^2:
2 x^2 + (x - 4 x) + (-11 + 17)
x - 4 x = -3 x:
2 x^2 + -3 x + (-11 + 17)
17 - 11 = 6:
Answer: 2 x^2 - 3 x + 6
Answer:
The value of x .
7x-14= 15x
-14 =8x
x= -7/4
Step-by-step explanation:
sorry if im wrong
Answer:
Your answer would be A
The site Math-way is a good tool for this
Answer:
It's 45.78
Step-by-step explanation:
4 x 10 = 40
5 x 1 = 5
7 x 1/10 = 0.7
8 x 1/100 = 0.08
add them all together and you get 45.78